EDTA-modified mesoporous silica as supra adsorbent of copper ions with novel approach as an antidote agent in copper toxicity - Taqanaki ER (Dove Medical Press, 2019)
Elham Rafiee Taqanaki,1 Reza Heidari,2 Mohammad Monfared,1,3 Lobat Tayebi,4 Amir Azadi,2,5 Fatemeh Farjadian2 1Department of Medical Nanotechnology, School of Advanced Medical Sciences and Technologies, Shiraz University of Medical Sciences, Shiraz, Iran; 2Pharmaceutical Sciences Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 3Student Research Committee, Shiraz University of Medical Sciences, Shiraz, Iran; 4School of Dentistry, Marquette University, Milwaukee, WI, USA; 5Department of Pharmaceutics, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Fatemeh FarjadianPharmaceutical Sciences Research Center, Faculty of Pharmacy, Shiraz University of Medical Sciences, P.O. Box 71345-1583, Shiraz, IranTel +987 113 242 4127 (302)Fax +98 713 242 4126Email farjadian_f@sums.ac.irAmir AzadiPharmaceutical Sciences Research Center, Department of Pharmaceutics, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, IranTel +987 113 242 4127 (286)Fax +98 713 242 4126Email aazadi@sums.ac.irPurpose: Mesoporous silica (MS) have been considered as a biocompatible compound and found to have various pharmaceutical applications. Recently, novel approaches in applications of MS as antidote agents were introduced. In this study, the capacity of ethylenediaminetetraacetic acid modified mesoporous silica (MS-EDTA) was evaluated in in vitro and in vivo adsorption of copper (Cu).Methods: The MS-EDTA was characterized by fourier transform infrared (FT-IR) and X-ray diffraction, while surface area was determined by N2 adsorption–desorption technique. Morphological studies were observed by high resolution-transmission electron microscopy and field emission-scanning electron microscopy and the sizes were determined by dynamic light scattering. The capacity of these particles for copper adsorption was investigated in vitro in both 1.2 and 7.2 pH. In in vivo animal study, the Cu adsorption efficiency of MS-EDTA in Cu-overdosed mice was evaluated. In this case, an animal model of acute copper poisoning was prepared.Results: The MS-EDTA with surface area of 352.35 was synthesized. Scanning electron microscope showed spherical particle formation with less than 500 nm in size. Transmission electron microscope images showed porous and honeycomb structure. FT-IR spectroscopy showed an appropriate formation of functional groups. Particle efficiency was investigated for Cu adsorption. MS-EDTA in both media showed a high adsorption capability for Cu (II) adsorption in pH=1.2 and pH=7.2. In addition, the study of Langmuir, Freundlich, and Redlich–Peterson adsorption models showed that copper adsorption by MS-EDTA followed the Freundlich model with multi-layer adsorption. In vivo evaluation showed that MS-EDTA could alleviate the symptoms of acute copper poisoning by lowering Cu plasma levels.Conclusion: Structural evaluation showed successful formation of MS-EDTA. In vitro analysis demonstrated that supreme Cu adsorption occurs in both pH conditions (7.2 and 1.2), and was especially more favorable in simulated intestinal pH (7.2). The in vivo studies in animal models with acute Cu poisoning showed that MS-EDTA could be a potent antidote agent.Keywords: mesoporous silica, antidote, copper, intoxication, EDTA, in vivo